2015
DOI: 10.1590/0034-737x201562060014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic leaf to evaluate the nutritional status of Jatropha

Abstract: RESUMOSubmitted on 07/07/2014 and aproved on 07/14/2015. 1 Embrapa Agropecuária Oeste, Dourados, Mato Grosso do Sul, Brazil. carlos.kurihara@embrapa.br; cesar.silva@embrapa.br *Corresponding author: carlos.kurihara@embrapa.br Diagnostic leaf to evaluate the nutritional status of JatrophaThe analytical determination of nutrient levels in recently mature leaves in order to diagnose nutritional status is based on the fact that leaves are metabolically active and more sensitive to variation in nutrients of the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The critical levels of nutrients in the physic nut leaves were compared with those proposed by Raviv and Lieth (2008) in plant tissues and medium concentrations found by Laviola and Dias (2008), Lima et al (2011b) and Kurihara and Silva (2015) on physic nut leaves.…”
Section: Calculations and Statisticsmentioning
confidence: 82%
See 4 more Smart Citations
“…The critical levels of nutrients in the physic nut leaves were compared with those proposed by Raviv and Lieth (2008) in plant tissues and medium concentrations found by Laviola and Dias (2008), Lima et al (2011b) and Kurihara and Silva (2015) on physic nut leaves.…”
Section: Calculations and Statisticsmentioning
confidence: 82%
“…In medium nutrient concentrations, Lima et al (2011b) reported that in physic nut plants the critical levels were low for the macronutrients and high for the micronutrients except to Zn, with low concentrations, when sampled leaves from the basal section of floral branches from fifth to tenth position from the apex without mentioning the position. For the average macronutrient concentrations in leaf samples located from the sixth to fifteenth position from the apex of floral branches in the middle third of physic nut, Kurihara and Silva (2015) found that, the critical levels were high for Ca, adequate for N and S and low for P, K and Mg. In this study, changes in the classification of critical levels of nutrients can be observed compared with other reports (Raviv and Lieth, 2008, Laviola and Dias, 2008, Lima et al, 2011band Kurihara and Silva, 2015.…”
Section: Critical Nutrient Levelmentioning
confidence: 97%
See 3 more Smart Citations